Incidence of electrocardiographic and electrolyte changes in acute oleander poisoning in humans: A systematic review and meta-analysis protocol - Asanka Eriyawa; Shaluka Jayamanne; Niroshan Lokunarangoda; Arunasalam Pathmeswaran; Rajeevan Francis; Kanagasingam Arulnithy; Dinuka Dharmapala; Pradeepa Jayawardane (PLoS ONE, 2025)
Yellow oleander (Cascabela thevetia, previously known as Thevetia peruviana) & Common oleander (Nerium oleander) contain a wide range of cardiac glycosides and their toxicity is similar to digoxin toxicity. It causes arrhythmogenesis by directly and indirectly influencing cardiac myocytes. Oleander poisoning leads to high morbidity and mortality, causing considerable healthcare burden worldwide. This systematic review and meta-analysis aim to synthesize evidence from studies reporting the effects of electrocardiographic and biochemical changes following acute oleander toxicity. It will contribute to identifying the true incidence of electrocardiographic and electrolyte changes which will be useful in-patient management and clinical decisions. Electronic databases, Google Scholar, and reference lists of relevant articles will be searched. Human studies reporting electrolyte and electrocardiographic changes following acute yellow oleander and common oleander toxicity globally from 1988 onwards will be included. The eligibility of studies will be checked by two reviewers independently, and the risk of bias will be evaluated for each study using the JBI critical appraisal tool. The Rayyan software will be used for the systematic review while heterogeneity of studies will be assessed using I2 statistics. In the case of I2 > 50%, meta-analysis will be conducted using a random effects model using STATA software. Publication bias will be assessed using visual inspection of funnel plots & Egger’s weighted regression. The incidence of electrocardiographic and biochemical changes following oleander poisoning will directly influence patient management and guide improvements in healthcare facilities. Although ethical approval is not required for the systematic review, it will be disseminated through peer-reviewed publications, index journals, and scientific conferences. PROSPERO registration PROSPERO registration number for this protocol is CRD42023451171